Catalytic Upgrading of Lignocellulosic Biomass Sugars Toward Biofuel 5-Ethoxymethylfurfural - Liu, Xiaofang; Yu, Dayong; Luo, Hangyu; Li, Can (Frontiers in Chemistry, 2022)
The conversion of biomass into high-value chemicals through biorefineries is a requirement for sustainable development. Lignocellulosic biomass (LCB) contains polysaccharides and aromatic polymers and is one of the important raw materials for biorefineries. Hexose and pentose sugars can be obtained from LCB by effective pretreatment methods, and further converted into high-value chemicals and biofuels, such as 5-hydroxymethylfurfural (HMF), levulinic acid (LA), γ-valerolactone (GVL), ethyl levulinate (EL), and 5-ethoxymethylfurfural (EMF). This mini-review summarizes the mechanism of several important processes of EMF production from LCB-derived sugars and the research progress of acid catalysts used in this reaction in recent years. The influence of the properties and structures of mono- and bi-functional acid catalysts on the selectivity of EMF from glucose were discussed, and the effect of reaction conditions on the yield of EMF was also introduced.